Osler goes viral: "The Fixed Period" revisited. Issue 4 (2nd October 2018) - Bryan, Charles S.
Abstract: William Osler's parting address to faculty at the Johns Hopkins University, given on February 22, 1905, and published as "The Fixed Period, " clouded his departure from North America after reporters sensationalized a playful suggestion that aging professors be chloroformed. A newly available collection of newspaper clippings affords a semiquantitative analysis of the press reaction. Only 40% of the writers openly criticized Osler. Some (about 15%) defended him; many (33%) merely attempted humor; and a few (about 6%) wrote poetry. Often overlooked are the main points of Osler's address: awareness of one's place in the adult life cycle and the need for self-renewal with advancing age.